Model Pembelajaran Hybrid dalam Mata Kuliah Analisis Investasi: Studi Persepsi Mahasiswa Program Studi Pendidikan Ekonomi - Sholihah, Nuro; Majdi, Muhammad Zainul; Ali, Muhamad (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to explore students’ perceptions of the hybrid learning model (a combination of online and face-to-face instruction) in the Investment Analysis course. The course was delivered in two phases: limited in-person meetings and independent assignment-based learning during the students’ community service program (KKN). A descriptive quantitative approach was applied using a Likert-scale questionnaire. The respondents consisted of 32 sixth-semester students from the Economic Education Study Program at Universitas Hamzanwadi enrolled in the 2024/2025 academic year. Descriptive statistics were used to analyze students’ perceptions of comfort, learning effectiveness, and challenges during hybrid instruction. The findings revealed that most students appreciated the flexibility of hybrid learning, especially in managing study schedules during KKN. However, many also experienced difficulties in mastering technical materials such as NPV, IRR, and Payback Period when studying independently. These results suggest that hybrid learning can be an effective alternative in constrained learning conditions, provided it is supported by adequate digital resources and structured academic guidance. This research is expected to contribute to the development of more effective hybrid learning strategies, especially for courses that require analytical and numerical understanding